Prediction of psychological outcomes one year after a motor vehicle accident. - Mayou, R; Bryant, B; Ehlers, A (2001)
OBJECTIVE: The authors' goal was to identify predictors of 1-year outcomes for consecutive patients in a hospital emergency department following motor vehicle accidents and to describe the prevalence and course of four types of psychiatric outcomes after such accidents. METHOD: Consecutive patients aged 17-69 years who attended a general hospital emergency department following a motor vehicle accident were identified. Medical information for these patients was extracted from case notes, and the patients completed self-report questionnaires at baseline (soon after the accident), 3 months after the accident, and 1 year after the accident. Measures included a self-report scale for posttraumatic stress disorder (PTSD), the Hospital Anxiety and Depression Scale, and questions about phobic travel anxiety. Logistic regression was used to examine predictors of outcome. RESULTS: Different frequencies and courses of PTSD, phobic travel anxiety, general anxiety, and depression were reported by a third of the subjects at both 3-month and 1-year follow-up. Many of the subjects reported improvements between 3 and 12 months, but others described late onset of psychiatric outcomes after the accident. There were differences in baseline and 3-month predictors of each type of 1-year outcome. CONCLUSIONS: The four types of psychiatric outcomes after a motor vehicle accident that were noted overlap, are persistent, and have different early predictors. These findings have implications for the early recognition of psychiatric consequences of motor vehicle accidents that would enable early intervention.